The Effectiveness of FSA on Fee Service Summary Rates in Hospital - Yunus, Restu; Nurhasanah, Nurhasanah; Audy Nabilla Caroline; Gregorius Fernando Jalung (Sean Institute, 2022)
Fee service was a component of hospital rates in the form of rewards received by staff for services provided to patients that affect performance and satisfaction of work. Effective management influences a hospital’s productivity in health services to patients. The aim of this study was to determine the effectiveness of the FSA (Fee Service-App) on rates of fee service summary in hospital. This study was a quasi-experimental design with a one-shot case study. Samples consisted of 183 financial data of inpatients at hospital in Samarinda City. Data analyzed were an independent t-test. The result of the study showed that the input duration level on FSA was 95% at the fast level and table application was 78% at the middle level. Rates of fee service summary with FSA was 99% at the fast level and table application was 92% at the slow level. In conclusion, there was a statistically significant difference between rates of fee service summary used FSA and the conventional table application.